2018
DOI: 10.1097/bpo.0000000000000774
|View full text |Cite
|
Sign up to set email alerts
|

Forearm Fixation is Not Necessary in the Treatment of Pediatric Floating Elbow

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Distal forearm association was more prevalent with subdivision into metaphyseal and physeal distal radius fractures. The location of the fracture in the proximal forearm suggested more traumatic force [ 9 , 10 ]. Moreover, it could be an open or closed injury.…”
Section: Discussionmentioning
confidence: 99%
“…Distal forearm association was more prevalent with subdivision into metaphyseal and physeal distal radius fractures. The location of the fracture in the proximal forearm suggested more traumatic force [ 9 , 10 ]. Moreover, it could be an open or closed injury.…”
Section: Discussionmentioning
confidence: 99%
“…Blumberg et al concluded that a floating elbow could be safely managed with operative stabilization of the supracondylar humerus fracture alone. 102…”
Section: Complicationsmentioning
confidence: 99%
“…Blumberg reviewed 47 children with supracondylar humeral fracture in which 21 of them had associated displaced forearm fracture; all the supracondylar fracture were managed surgically and all the forearm were immobilized with noncircumferential cast and none of those 21 children developed compartment syndrome. [42] Another recent retrospective review of 150 ipsilateral supracondylar humerus and forearm fractures did not identify any compartment syndrome in these children. [43] There is controversy in which fracture to fix first and whether to fix humeral fracture and to conservatively manage the forearm fracture but rigid stable fixation of all the fractures has been accepted as the best choice for the treatment of floating elbow injuries.…”
Section: Floating Elbowmentioning
confidence: 99%